Azithromycin modulates neutrophil function and circulating inflammatory mediators in healthy human subjects - Čulić, Ognjen; Eraković, Vesna; Čepelak, Ivana; Barišić, Karmela; Brajša, Karmen; Ferenčić, Željko; Galović, Ružica; Glojnarić, Ines; Manojlović, Zoran; Munić, Vesna; Novak-Mirčetić, Renata; Pavičić-Beljak, Verica; et al. (European journal of pharmacology, 2002)
Effects on human neutrophils and circulating inflammatory mediators were studied in 12 volunteers who received azithromycin (500 mg/day, p.o.) for 3 days. Blood was taken 1 h before treatment, 2.5, 24 h and 28 days after the last dose. An initial neutrophil degranulating effect of azithromycin was reflected in rapid decreases in azurophilic granule enzyme activities in cells and corresponding increases in serum. The oxidative response to a particulate stimulus was also acutely enhanced. These actions were associated with high plasma and neutrophil drug concentrations. A continuous fall in chemokine and interleukin-6 serum concentrations, within the non-pathological range, accompanied a delayed down-regulation of the oxidative burst and an increase in apoptosis of neutrophils up to 28 days after the last azithromycin dose. Neutrophils isolated from blood at this time point still contained detectable drug concentrations. Acute neutrophil stimulation could facilitate antibacterial effects of azithromycin, while delayed, potentially anti-inflammatory activity may curtail deleterious inflammation.